Faith, fictionalism and bullshit. (31st March 2020) - Scott, Michael
Abstract: According to a simple formulation of doxasticism about propositional faith, necessarily faith that p requires belief that p . Support of doxasticism is long‐standing and was rarely a matter of dispute until William Alston (1996) proposed that that the content of propositional faith need not be believed if it is accepted. Subsequently non‐doxastic theories that reject the belief requirement have proliferated and have come to dominate literature in the field. This paper aims to redress the balance by identifying a dilemma for non‐doxasticism that comes into view when we draw out the implications of non‐doxasticism for the interpretation of affirmations of religious propositional faith. One horn of this dilemma commits non‐doxasticists to hermeneutic fictionalism: a substantive, contentious and little explored theory about religious discourse. The other appears to render the affirmation of faith prima facie bullshitting, leading to problems about the integrity of religious discourse and its speakers.